Being, living, thinking: metaphysics and philosophy as a way of life - Leung, King-Ho (2018)
This thesis examines the relationship between metaphysical theorisation and the practice of philosophy as a way of life. The thesis begins by highlighting the parallels between the Cartesian shift away from the premodern practice of philosophy as a way of life (what Foucault terms ‘the Cartesian moment’) and the ontological suspension of ‘life’ in Descartes’ influential re-conception of the soul as the principle of thinking instead of life and in his mechanistic understanding of living beings as automata. After this, it examines the works of Martin Heidegger, Heidegger’s former students Hannah Arendt and Giorgio Agamben, as well as Gilles Deleuze (and via Deleuze, Henri Bergson) and considers how the metaphysical theoretical conception of ‘being’, ‘living’ and ‘thinking’ informs and affects the practice of philosophy. The thesis concludes with a re-reading of Augustine’s philosophy of life in light of these contemporary philosophical developments. By underscoring the connections between Augustine’s metaphysical conception of God as ‘Life itself’ and his philosophical practice of introspection as notably found in his Confessions—one of the most important texts of Western metaphysics and spiritual practice, this thesis argues that metaphysical theorisation is in fact not incompatible with the premodern practice of philosophy as a way of life or spiritual exercise (as suggested by Foucault and to some extent Heidegger). Instead, Augustine’s Christian appropriation of the Platonic metaphysics of participation in light of his philosophical interpretation of the Christian doctrine of the incarnation not only shows us how speculative metaphysics can provide a powerful theoretical incentive to lead a philosophical life, but also how a ‘religious’ approach to philosophising can help recover the understanding of philosophy as way of life and furthermore reconcile the supposed division between metaphysical theorisation and the practice of philosophy as a way of living.